Do the Advantages of a Minimally Invasive Approach Remain in Complex Colorectal Procedures? A Nationwide Comparison. Issue 4 (April 2015) - Schlussel, Andrew T.; Lustik, Michael B.; Johnson, Eric K.; Maykel, Justin A.; Champagne, Brad J.; Goldberg, Joel E.; Steele, Scott R.
Abstract : BACKGROUND: Since the introduction of laparoscopic colectomy, experience and technology continue to improve. Although accepted for many colorectal conditions, its use and outcomes in complex procedures are less understood. OBJECTIVE: The purpose of this work was to compare the perioperative outcomes of laparoscopic transverse colectomy and total abdominal colectomy (study group) with an open approach (comparative group) and the more established laparoscopic right, left, and sigmoid colectomies (control group). DESIGN: This was a retrospective review of the Nationwide Inpatient Sample (2008–2011) of all patients undergoing elective right, left, sigmoid, total, or transverse colectomy as identified by International Classification of Diseases, Ninth Revision, Clinical Modification procedure codes. Risk-adjusted 30-day outcomes were assessed using regression modeling accounting for patient characteristics, comorbidities, and surgical procedures. SETTINGS: The study included a national sample from a population database. PATIENTS: There were 45, 771 admissions: 2946 in the study group, 36, 949 in the control group, and 5876 in the open comparative group. MAIN OUTCOME MEASURES: Mortality was the primary outcome. Secondary outcomes included in-hospital complications, length of stay, and hospital charges. RESULTS: The patients were predominantly white (73%), had private insurance (64%), and underwent surgery at urban centers (92%). Mortality was similar between the study and control groups (0.42% vs 0.51%; p = 0.52), with a higher complication rate in the study group (19% vs 14%; p < 0.01). The study group was also associated with a lower mortality rate compared with the open group (0.51% vs 2.20%; p < 0.01), which remained consistent after adjusting for covariates (OR, 0.38 [95% CI, 0.20–0.71]; p < 0.01). The study group had fewer complications overall compared with the open group (19% vs 27%; p < 0.01) and a shorter median length of stay (4.6 vs 6.3 days; p < 0.01). LIMITATIONS: This was a retrospective study using an administrative database. CONCLUSIONS: A laparoscopic approach for total abdominal and transverse colectomies has similar mortality rates and slightly higher complications than the more established laparoscopic colectomy procedures and improved perioperative outcomes when compared with an open technique (see Video, Supplemental Digital Content 1, http://links.lww.com/DCR/A178 ). Abstract : Supplemental Digital Content is available in the text.